Direct observation of the strange b baryon Xi(-)(b) - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2007)
We report the first direct observation of the strange b baryon Xi(-)(b)(Xi) over bar (+)(b)). We reconstruct the decay Xi(-)(b)-->J/psi Xi(-), with J/psi-->mu(+)mu(-), and Xi(-)-->Lambda pi(-)-->p pi(-)pi(-) in p (p) over bar collisions at root s = 1.96 TeV. Using 1.3 fb(-1) of data collected by the D0 detector, we observe 15.2 +/- 4.4(stat)(-0.4)(+1.9)(syst) Xi(-)(b) candidates at a mass of 5.774 +/- 0.011(stat) +/- 0.015(syst) GeV. The significance of the observed signal is 5.5 sigma, equivalent to a probability of 3.3 x 10(-8) of it arising from a background fluctuation. Normalizing to the decay Lambda(b)-->J/psi Lambda, we measure the relative rate sigma(Xi(-)(b))xB(Xi(-)(b)-->J/psi Xi)/ sigma(Lambda(b))xB(Lambda(b)-->J/psi Lambda) = 0.28 +/- 0.09(stat)(-0.08)(+0.09)(syst).